Persepsi Manfaat, Kemudahan Penggunaan dan Minat Menggunakan Internet Banking dengan Sikap Sebagai Variabel Intervening - Mahesa Arsita Putri, Ni Putu; Agung Suaryana, I Gusti Ngurah (E-Jurnal Akuntansi; Vol 31 No 6 (2021), 2021)
This study aims to determine the effect of perceived usefulness and ease of use on interest in using BRI internet banking with the role of attitude as an intervening variable. The analysis technique used is Structural Equation Modeling (SEM) with a variance based or component based approach with Partial Least Square (PLS). The results of this study indicate that, Perception of benefits has a positive and significant effect on attitudes, Ease of use has a positive and significant effect on attitudes, Perception of benefits has a positive and significant effect on interests, Ease of use has a positive and significant effect on interests, Attitude has positive and significant effect on interest, Perception of benefits has positive and significant effect on interest through attitude as avriable intervening, Ease of use has positive and significant effect on interest through attitude as attitude as intervening variable. Keywords: Perception of Benefits; Ease of Use; Attitude; Interest.